O brincar, o brinquedo e a brincadeira no Baixo Tocantins - CARDOSO, Alessandra de Lima (2022)
The present work exposes and discusses aspects of play, toy and play in Baixo Tocantins. The research was carried out in the municipalities of Abaetetuba, Barcarena and Moju, Panacuera River / Abaetetuba Island (Baixo Tocantins regions). It is intended to show the importance of playing in the teaching-learning process, in the socialization and experiences of an authentic childhood, rescuing memories, in order to understand and maintain the meaning and relevance of play, toys and games for children. Giving a voice to them is understood their conception of play and the value that the game has for them, we also report experiences of the group about childhood experiences. Using as theoretical-methodological basis authors such as: Eliana Pojo, Waldir Abreu, Damião Oliveira, Wanderleia Leitão, Sônia Kramer and Gilles Brougére. In order to better understand the subject and achieve the proposed objectives, we use bibliographical research and field research with a qualitative approach, analyzing the main theoretical contractions and seeking a better approximation with the environment and the perspective of the subject, with participant observation as the main instrument of data collection. Using as an interview method with children and adults, for this research were interviewed two educators between the ages of 20 and 40 years. It presents the concept of play as an instrument of cultural valorization, formation of identity and manifestation of values of a society. Through the games, the children know and adapt to the social environment, playing with their reality - a river child plays catching açaí, fishing; games related to the land, to water, which refer to their daily life, what surrounds them. Thus, playfulness allows the approximation of social and cultural codes, through the representations and imaginary associations linked to playing, giving the child the encounter between fantasy and reality, fun and learning. Through the interviews and surveys we gathered and listed the main games between children, the toys used and the ways of playing. In the results appear jokes such as: hopscotch / macaca, sweater / burnt whitney, falls in the well, pirate hides / hide-andseek, high pirate, pyre cola, among others. With the reports of the group about their childhood they notice the differences between the play of before and the play of today, as the change in the way of playing, in the name of games previously known of other forms and the difficulty to find traditional games . Finally, it is emphasized the importance of socializing the knowledge of games and games of our childhood with the children of today, turning our eyes to the children of the region of Baixo Tocantins, not letting the practice and the culture of play disappear of the reality of these, given their importance in various educational and cultural aspects.